Cost of Open access publishing in the light of global developments in scholarly publishing: Springer’s Open access initiative - Friedman, Megan (Septentrio Conference Series, 2014)
>> See video of presentation (25 min.) BioMed Central is the open access publisher who pioneered this publishing model and has been part of Springer since 2008. We launched our first journal in the year 2000, and have since seen several positive global developments which have helped establish open access as an important trend in the evolvement of scholarly communication. We have consequently observed a steady increase in awareness of open access and specifically, of our wide range of specialist as well as broad interest titles which is reflected in our growing submission numbers. BioMed Central as one of the main open access publishers has helped to establish open access as a new way of making academic research available to researchers and the public, and to introduce a change of the subscription business model in academic publishing and libraries. While BioMed Central also offers a solution for the Green Route of open access (“Open Repository”) the main part of our publishing activity is centred around our fully or “gold” open access journals. BioMed Central and SpringerOpen practise the “author pays” model, whereby the author is asked to pay a fee to cover the publisher’s cost of publishing and distributing the article. While the awareness of open access is growing among the academics, there is still uncertainty among many of how open access works and why they are asked to pay a fee. To cover that fee can still be a major obstacle for a researcher attempting to publish an article in an open access journal, as the SOAP report stated in 2011. I will present an analysis of the most recent open access developments and studies globally; as well as the effect that this has had on a number of factors that play a role in scholarly publishing, such as Impact Factors, citations and awareness of open access among academics. I will give an update on BioMed Central and Springer’s own development in the arena of open access and visibility of research, including experimenting with alternative methods of evaluating research such as Altmetric and the SCImago Journal & Country Rank. I will conclude with an overview of how we are working with research organisations and universities to offer financial support to their researchers in order to cover the fee for publishing in BioMed Central and SpringerOpen journals in the context of our institutional membership program.